Diterpenoids from Plectranthus spp. as Potential Chemotherapeutic Agents via Apoptosis - Tomasz Śliwiński; Przemysław Sitarek; Ewa Skała; Vera M. S. Isca; Ewelina Synowiec; Tomasz Kowalczyk; Michał Bijak; Patrícia Rijo (MDPI AG, 2020)
Plectranthus spp. is widely known for its medicinal properties and bioactive metabolites. The cytotoxic and genotoxic properties of the four known abietane diterpenoids: 7α-Acetoxy-6β-hydroxyroyleanone (Roy), 6,7-dehydroroyleanone (Deroy), 7β,6β-dihydroxyroyleanone6 (Diroy), and Parvifloron D (Parv), isolated from P. madagascariensis (Roy, DeRoy, and Diroy) and P. ecklonii (Parv) were evaluated. The tested compounds showed cytotoxic effects against the human leukemia cell line CCRF-CEM and the lung adenocarcinoma cell line A549. All tested compounds induced apoptosis by altering the level of pro- and anti-apoptotic genes. The results show that from the tested diterpenoids, Roy and Parv demonstrated the strongest activity in both human cancer cell lines, changing the permeability mitochondrial membrane potential and reactive oxygen species (ROS) levels, and possibly inducing mtDNA or nDNA damage. In conclusion, the abietane diterpenoids tested may be used in the future as potential natural chemotherapeutic agents